Morphological and genomic assessment of divergence between closely related species of the genus Philaenus (Hemiptera, Aphrophoridae) - Seabra, Sofia (2020)
Philaenus spumarius, is a widespread and polyphagous xylem-feeding insect. It is also the main vector of Xylella fastidiosa in Europe (Saponari et al., 2014). P. spumarius and P. tesselatus are considered sister species, differentiated at the male genitalia level but not at karyological, mitochondrial DNA and some nuclear genes levels (Maryanska-Nadachowska et al., 2012; Rodrigues et al., 2014). Genome-wide markers revealed previously unreported genetic differentiation. Here we aim at characterising morphological variation in the male genitalia in both species.